Pengaruh Penerapan Sistem Informasi Online E-Samsat Jabar Terhadap Tingkat Kepatuhan Wajib Pajak Kendaraan Bermotor - Diah Oktavianingrum; Rendra Trisyanto Surya; Yeti Apriliawati (Indonesian Accounting Research Journal, 2021)
The purpose of this study was to determine whether there is an effect of the application of the West Java E-Samsat online information system on the compliance level of motorized vehicle taxpayers registered at the Samsat Bandung I Pajajaran Office and how much influence it has. The type of research approach used is quantitative. The population of this research is private ownership of taxpayers of two-wheeled motor vehicles and four-wheeled vehicles. The sample was determined by a purposive sampling method of 100 motor vehicle taxpayers registered at the Samsat Bandung I Pajajaran Office. The data collection technique used in this study was a questionnaire that had been tested for validity and reliability. The data analysis technique used to answer the hypothesis is simple linear regression. The results of data analysis are seen from the results of the determination coefficient test, to find out how big the contribution given by the West Java E-Samsat online information system to the compliance level of motor vehicle taxpayers is 72.6%. Furthermore, the results of hypothesis testing can be seen that the t-count value is 16.115 and the t-table value is known to be 1.966. Therefore, through the results of hypothesis testing, which means that the value of t is greater than t table (16.115> 1.966). Thus the result is that H0 is rejected and Ha is accepted. Therefore there is a positive and significant influence between the West Java E-Samsat online information system on the level of motor vehicle taxpayer compliance.